Interval‐induced metabolic perturbation determines tissue fluid shifts into skeletal muscle. Issue 7 (27th April 2021) - Mandić, Mirko; Forsgren, Mikael F.; Romu, Thobias; Widholm, Per; Sundblad, Patrik; Gustafsson, Thomas; Rullman, Eric
Abstract: Intense interval exercise has proven to be as effective as traditional endurance exercise in improving maximal oxygen uptake. Shared by these two exercise regimes is an acute reduction in plasma volume, which is a suggested stimulus behind exercise‐induced increases in blood volume and maximal oxygen uptake. This study aimed to link exercise‐induced metabolic perturbation with volume shifts into skeletal muscle tissue. Ten healthy subjects (mean age 33 ± 8 years, 5 males and 5 females) performed three 30 s all‐out sprints on a cycle ergometer. Upon cessation of exercise magnetic resonance imaging, 31 Phosphorus magnetic resonance spectroscopy and blood samples were used to measure changes in muscle volume, intramuscular energy metabolites and plasma volume. Compared to pre‐exercise, muscle volume increased from 1147.1 ± 35.6 ml to 1283.3 ± 11.0 ml 8 min post‐exercise. At 30 min post‐exercise, muscle volume was still higher than pre‐exercise (1147.1 ± 35.6 vs. 1222.2 ± 6.8 ml). Plasma volume decreased by 16 ± 3% immediately post‐exercise and recovered back to – 5 ± 6% after 30 min. Principal component analysis of exercise performance, muscle and plasma volume changes as well as changes in intramuscular energy metabolites showed generally strong correlations between metabolic and physiological variables. The strongest predictor for the volume shifts of muscle and plasma was the magnitude of glucose‐6‐phosphate accumulation post‐exercise. Interval training leads to large metabolic and hemodynamic perturbations with accumulation of glucose‐6‐phosphate as a possible key event in the fluid flux between the vascular compartment and muscle tissue. Abstract : Here we show that skeletal muscle metabolic perturbation after a bout of high intensity interval exercise correalltes with plasma‐volume drop and a corresponding increase in muscle volume.